The family, "holonized" entity. (Journal of Parents and Teachers, 2025)
The article expresses that the family is distinguished into three holons: the conjugal, parent-child, and sibling holons, where each has its own space to progress both personally and in communication. It also mentions a series of items to consider, including that each member belongs to a family subsystem, that there should be no comparisons, and that reality must be accepted.
Keywords: holons; family; reality; progress